Depopulation in the Baltic States - Berzins, Atis; Zvidrins, Peteris (Lithuanian Journal of Statistics, 2011)
The paper deals with the characterization of the main demographic processes in the Baltics. After the reestablishmentof statehood in Estonia, Latvia and Lithuania, the population dynamics clearly have been decreasing. This isevidenced both by the negative results of natural movement and the dominance of emigration in international migration processes.Population decline (depopulation) is a characteristic feature also for the titular ethnicities. Under-replacement fertility,relatively high mortality, especially for men, a high intensity of emigration and an ageing population are observed in all threeBaltic countries, particularly after accession to the European Union in 2004. Latvia and Lithuania since 1990 have had amongthe highest population loss indicators in Europe. The scenarios of depopulation still prevail in the coming decades.
Keywords: depopulation; ageing; fertility; mortality